2015
DOI: 10.1080/17501229.2015.1043915
|View full text |Cite
|
Sign up to set email alerts
|

Peer-mediated vs. individual writing: measuring fluency, complexity, and accuracy in writing

Abstract: Drawing upon Vygotsky's Sociocultural Theory (SCT), this study aimed at investigating the effect of two writing modes, namely, peer-mediated/collaborative vs. individual writing on measures of fluency, accuracy, and complexity of female EFL learners' writing. Based on an in-house placement test and the First Certificate in English writing paper, a total of 108 intermediate (N = 54) and advanced (N = 54) participants out of a pool of 150 EFL learners were randomly selected and assigned equally to collaborative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…e results are in line with Wiggleworth and Storch [27] that investigated the advantages of collaborative writing where they found that collaboration had a positive effect on accuracy. e results also confirm the results by Soleimani et al [32] who investigated the effect peer-mediated/collaborative and individual writing on female EFL learners' writing fluency, accuracy, and complexity and found that collaborative groups outperformed the individual groups in fluency and accuracy, but not in complexity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…e results are in line with Wiggleworth and Storch [27] that investigated the advantages of collaborative writing where they found that collaboration had a positive effect on accuracy. e results also confirm the results by Soleimani et al [32] who investigated the effect peer-mediated/collaborative and individual writing on female EFL learners' writing fluency, accuracy, and complexity and found that collaborative groups outperformed the individual groups in fluency and accuracy, but not in complexity.…”
Section: Discussionsupporting
confidence: 90%
“…Soleimani et al [32] investigated the effect of two writing conditions, namely, peer-mediated/collaborative vs. individual writing on female EFL learners' writing fluency, accuracy, and complexity. A two-way analysis of variance statistics revealed that, across both proficiency levels, collaborative groups outperformed the individual groups in terms of fluency and accuracy, but not in complexity.…”
Section: Related Empirical Studiesmentioning
confidence: 99%
“…Besides, the mixed findings in the efficacy of peer feedback by Ghahari and Farokhnia (2018) and Shang (2019) used these indexes on writing complexity, accuracy, and fluency. Rather, studies by Soleimani and Rahmanian (2014) and Rayati (2014) extricated from these findings by comparing self-, peer-, and teacher-assessments through CAF measures to reveal differential gains from differently Rseltl.pierreonline.uk formatted feedback. On the one hand, these studies inform a peer response's potential for improving writing motivation; on the other hand, they re-emphasize the need for methodological refinements and careful use of CAF indices, since the indices have been found to be too sensitive to textual variables like length of the text.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They highlighted the fact that peer corrections were significant, explicitly stating that peer revision should be seen as an important additional type of feedback for EFL learners as peer feedback was more closely associated with linguistic rather than pragmatic aspects of writing (Hyland and Hyland 2019). Soleimani et al (2017) also explored the impact of peer-mediated/collaborative versus individual writing on measures of fluency, accuracy, and complexity of 150 female EFL learners' texts. Their findings revealed that collaborative groups outperformed the individual groups in terms of fluency and accuracy but not in terms of complexity.…”
Section: Pa and Writing Qualitymentioning
confidence: 99%
“…This enabled the creation of a community of learning where learners helped their classmates improve their writing skills. In their exciting journey from almost ignorant assessors to knowledgeable evaluators, learners managed to familiarise themselves with the rules of their community, communicate with their peers, and play their distinct roles as assessors and assessees (also in Simeon 2014). This is a procedure that is worthwhile using in EFL and other subjects in Cyprus, but also worldwide.…”
Section: Conclusion and Pedagogical Implicationsmentioning
confidence: 99%